Can EAT be an INOCA goalkeeper - Shan, Tong; Shuwen, Zheng; Hengbin, Wu; Min, Zeng (Frontiers in Endocrinology, 2023)
Ischemia with non-obstructive coronary heart disease (INOCA) is a blind spot of coronary heart disease. INOCA is not accurately assessed, which puts patients at a higher risk of cardiovascular death. EAT is proven to correlate independently with atherosclerosis severity in thickness and volume, but it is unknown whether EAT is specific and a sensitive indicator of intractable coronary artery disease. This review focuses on the INOCA epidemiology and related factors, as well as the association between EAT and INOCA.